MORFEM-MORFEM PEMBENTUK VERBA DASAR TRILITERAL BAHASA ARAB - Mohamad Afrizal; Amir Ma'ruf (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2014)
Arabic verbs are polymorphemic. Among the Arabic verbs are verbs called basic triliteral verbs. In addition to the root morpheme, there are other morphemes contained in basic triliteral verbs. This study attempts to examine the number and forms of morphemes contained in basic triliteral verbs, which have been much debated. In addition, this study also discusses the morphological, and morphophonological processes and the meaning of morphemes forming the basic triliteral verbs. The data were collected through observation of the conjugation of basic triliteral verbs and of the meanings of the verbs in an Arabic-Indonesian dictionary. Distributional and translational equivalent methods were used to analyze the data. The results reveal that basic triliteral verbs in Arabic are composed of the root morpheme, transfix, and affix of person, number and gender. The morphological process of a basic verb triliteral begins with the transfixation of root morpheme that becomes a base, followed by affixation of person, number and gender. The morphological process can lead to phonological changes. This morphophonological process involves the phonemes /w/, /y/, /`/ and gemination as part of the root morpheme.